2005
DOI: 10.1080/10611860400011935
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric micelles for delivery of poorly soluble drugs: Preparation and anticancer activityin vitroof paclitaxel incorporated into mixed micelles based on poly(ethylene glycol)-lipid conjugate and positively charged lipids

Abstract: Paclitaxel-loaded mixed polymeric micelles consisting of poly(ethylene glycol)-distearoyl phosphoethanolamine conjugates (PEG-PE), solid triglycerides (ST), and cationic Lipofectin® lipids (LL) have been prepared. Micelles with the optimized composition (PEG-PE/ST/LL/paclitaxel = 12/12/2/1 by weight) had an average micelle size of about 100 nm, and zeta-potential of about 26 mV. Micelles were stable and did not release paclitaxel when stored at 4°C in the darkness (just 2.9% of paclitaxel have been lost after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 46 publications
4
79
0
1
Order By: Relevance
“…Recently, drug delivery systems have been engineered for the delivery of Ptx. [22][23][24] However, in a preliminary study, it was found that Ptx-loaded nanoparticles with amphilic copolymer as the carrier were unstable in the aqueous phase and were easy to aggregate. It was previously reported that Tet could effectively stabilize Ptx-loaded nanoparticles when it was coencapsulated with Ptx.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, drug delivery systems have been engineered for the delivery of Ptx. [22][23][24] However, in a preliminary study, it was found that Ptx-loaded nanoparticles with amphilic copolymer as the carrier were unstable in the aqueous phase and were easy to aggregate. It was previously reported that Tet could effectively stabilize Ptx-loaded nanoparticles when it was coencapsulated with Ptx.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, an attempt was made to increase the intracellular delivery and thus the anticancer activity of the micellar paclitaxel by preparing paclitaxel-containing micelles from the mixture of PEG-PE and Lipofectin lipids (LL). 217 When the cellular uptake of various fl uorescently labeled micelles in adherent BT-20 cells was studied, it was found that while both " plain " PEG-PE micelles and PEG-PE/LL micelles were endocytosed by BT-20 cells, as confi rmed by the presence of fl uorescent endosomes in cells after 2 hours of co-incubation with fl uorescently labeled micelles, in case of PEG-PE/LL micelles, endosomes became partially disrupted and their content was released into the cell cytosol. The addition of LL, facilitating the intracellular uptake and cytoplasmic release of paclitaxel-containing PEG-PE/LL micelles, resulted in a substantially increased level of cell death compared with that under the action of free paclitaxel or paclitaxel delivered using noncationic LL-free PEG-PE micelles.…”
Section: Ph-sensitive Carriersmentioning
confidence: 99%
“…Such systems must load and 28 stably retain anticancer drugs and must also have a means to 29 release drugs into cells. Anticancer drug delivery systems have 30 thus far included bioconjugates (1-3), nanoparticles (4,5), 31 liposomes (6,7), polymersomes (8)(9)(10), and polymeric micelles 32 composed of amphiphilic block copolymers (11,12), but all of 33 the cited carriers are essentially spherical in shape. Long and 34 flexible Bworm-like^micelle carriers made from amphiphilic 35 block copolymers are described here in terms of formulation 36 and in vitro delivery, and the findings follow up on recent 37 studies that demonstrate surprisingly persistent circulation and 38 potent anti-tumor activity of worm-like micelles in vivo (13).…”
Section: Research Papermentioning
confidence: 99%